Ganglionic Acetylcholine Receptor Antibodies in Postural Tachycardia Syndrome. Issue 4 (August 2021) - Bryarly, Meredith; Raj, Satish R.; Phillips, Lauren; Hynan, Linda S.; Okamoto, Luis E.; Arnold, Amy C.; Paranjape, Sachin Y.; Vernino, Megan; Black, Bonnie K.; Vernino, Steven
Abstract : Objective: Postural tachycardia syndrome (POTS), the most common form of dysautonomia, may be associated with autoimmunity in some cases. Autoantibodies against the ganglionic acetylcholine receptor (gAChR) have been reported in a minority of patients with POTS, but the prevalence and clinical relevance is unclear. Methods: Clinical information and serum samples were systematically collected from participants with POTS and healthy control volunteers (n = 294). The level of positive gAChR antibodies was classified as very low (0.02–0.05 nmol/L), low (0.05–0.2 nmol/L), and high (>0.2 nmol/L). Results: Fifteen of 217 patients with POTS (7%) had gAChR antibodies (8 very low and 7 low). Six of the 77 healthy controls (8%) were positive (3 very low and 3 low). There were no clinical differences between seropositive and seronegative patients with POTS. Conclusions: Prevalence of gAChR antibody did not differ between POTS and healthy controls, and none had high antibody levels. Patients with POTS were not clinically different based on seropositivity. Low levels of gAChR antibodies are not clinically important in POTS.